The Effect of Playing Mpa’a Tapa Gala Game Toward Gross Motor Development on Early Childhood (Universitas Negeri Semarang, 2019)
Traditional mpa'a tapa gala game was a team game that consist of a playing team and guarding team. Mpa'a tapa gala game was modified to determine the comparison level of results and influence to early childhood children in then gross motor development. This study aims to: (1) Recognite the play and game of mpa’a tapa gala (traditional and modification) toward the gross motoric development of children; (2) Understanding the difference between the results of gross motor development through playing and the game of mpa'a tapa gala (traditional and modification); (3) Knowing the effect of interaction between learning through play and game of mpa'a tapa gala (traditional and modification) on increasing gross motor development. This research method was an experiment with the Pretest-Posttest Control Group Design. The sample was selected by using daily group assessment observations. This research method is an experiment with the Pretest-Posttest control group design research design. The results of the study show that: (1) There are significant differences in playing and game of mpa’a tapa gala (traditional and modification) to the gross motoric development of children. This case can be seen from the percentage test of experimental and control groups playing without traditional mpa’a tapa gala and modification of the three movements (locomotor, non-locomotor, and manipulative) achieving completeness individuals above 70 untill 100 so that the classical completeness reaches 100%, statistical analysis of the three average movements of tvalue ≤ ttable, and sig 2 (tailed) the third average of movement 0.00 ≤ 0.05; (2). There is a significant difference in gross motoric development through mpa'a tapa gala playing game (traditional and modification); (3) There is a significant influence on the interaction of learning through playing and the game of mpa'a tapa gala (traditional and modification) on the increase in gross motor skills of early childhood.